Pendidikan Islam Multikultural dalam Menciptakan Integrasi Sosial: Pendidikan Islam Multikultural dalam Menciptakan Integrasi Sosial - Anton, Anton; Azizah, Dalfa; Dini, Selvi Aula; Tauzirie, Muhamad Faridz; Iman, Fajar (UNIVERSITAS SERAMBI MEKKAH, 2025)
Cultural, religious, and ethnic diversity is both a wealth and a challenge for the Indonesian nation. In this context, multicultural Islamic education offers a strategic solution to build social integration in a pluralistic society. This study aims to explore the implementation of multicultural Islamic education in supporting social integration, identify relevant values ​​such as tolerance, peace, and respect for diversity, and examine the challenges in its implementation. The method used is a literature review with a descriptive-analytical approach to the latest academic literature. The results of the study indicate that multicultural Islamic education is able to create social harmony through the integration of universal values ​​in the curriculum, cross-cultural dialogue, and strengthening tolerance. However, challenges such as low teacher competence and cultural resistance are still obstacles. This study contributes to formulating an effective implementation strategy for multicultural Islamic education to create an inclusive and just society.